Watching “Wonder Woman”: Reception of an American Film by Youth in Indonesia - Az-Zahroh, Fatimah; Habsari, Sri Kusumo (Jurnal Bahasa, Sastra, dan Studi Amerika, 2022)
The popularity of Wonder Woman (2017) movie worldwide is not only reached the western lands but also the eastern countries, including Indonesia. Wonder Woman offers western post-feminist idea which can bring various responses to the audiences in Indonesia. By using descriptive qualitative approach, this research explores how the young audiences in Indonesia take pleasure and make meaning to the element of feminism in the movie. This research finds that Gal Gadot’s Diana performance in the movie offers special spectacle to the audience through her feminine qualities, such as beautiful face, ideal female body, and gentle character, despite being a powerful female hero who also has the quality of courage, strong determination, athleticism, and skill in fighting. The duality of Diana’s character, the femininity and masculinity, is also noted by the audiences as one of the most notably signs which presented feminism in the movie. Although most of the audiences are Muslim and embrace eastern culture, they tend to be more open to the feminist signs in the movie, as they have often been familiarized themselves with western values by frequently watching Hollywood movies.